2003
DOI: 10.2337/diacare.26.3.608
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alcohol Intake on Insulin Sensitivity in Men

Abstract: OBJECTIVE -Population data suggest that alcohol consumption may influence the risk of diabetes in a biphasic manner, but this has not been tested by any controlled interventions. The object of this study was to determine whether reducing alcohol intake in moderate-to-heavy drinkers (40 -110 g/day) results in improvement in insulin sensitivity. RESEARCH DESIGN AND METHODS-A 4-week run-in period where subjects maintained their usual drinking pattern was followed by randomization to a two-way cross-over intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 31 publications
3
39
0
2
Order By: Relevance
“…5 Studies by other researchers show a negative association between insulin resistance and alcohol consumption. 11,20,[30][31][32][33] For example, studies by Kang et al 34 and…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Studies by other researchers show a negative association between insulin resistance and alcohol consumption. 11,20,[30][31][32][33] For example, studies by Kang et al 34 and…”
Section: Discussionmentioning
confidence: 99%
“…31,34 In their studies, however, rats consumed an ethanol-containing liquid diet, which contained high levels of fat. 32,34 Our results (Figure 3a) and those of others 19,35 show that a HFdiet can induce insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest that chronic light or heavy ethanol consumption leads to insulin resistance, whereas moderate ethanol consumption results in increased insulin sensitivity [37][38][39][40][41] . In the present study, we found that long-term high-dose ethanol consumption led to insulin resistance in rats, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Positive associations between alcohol consumption and insulin sensitivity are consistently reported in crosssectional studies (Kiechl et al, 1996;Bell et al, 2000), but randomized controlled studies report contradictory results (Cordain et al, 1997;Cordain et al, 2000;Davies et al, 2002;Zilkens et al, 2003;Beulens et al, 2006). Sierksma et al (2004) suggested that an increase of adiponectin could precede changes of insulin sensitivity with moderate alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%